Electrical equipment electrical production and distribution - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with basic concepts associated with the production and distribution of electric power for use by process systems. After completing this unit, trainees should be able to identify and explain the functions of the major components in an electrical distribution system. In addition, trainees should be able to describe general hazards associated with these systems and how to minimize the possible effects of the hazards.
Keywords: Electric power distribution -- High tension; Electric power transmission; Electric power distribution